Importance of a Fluorine Substituent for the Preparation of meta‐ and para‐Pentafluoro‐λ6‐sulfanyl‐Substituted Pyridines. Issue 36 (3rd August 2016) - Kosobokov, Mikhail; Cui, Benqiang; Balia, Andrii; Matsuzaki, Kohei; Tokunaga, Etsuko; Saito, Norimichi; Shibata, Norio
Abstract: Although there are ways to synthesize ortho ‐pentafluoro‐λ 6 ‐sulfanyl (SF5 ) pyridines, meta ‐ and para ‐SF5 ‐substituted pyridines are rare. We disclose herein a general route for their synthesis. The fundamental synthetic approach is the same as reported methods for ortho ‐SF5 ‐substituted pyridines and SF5 ‐substituted arenes, that is, oxidative chlorotetrafluorination of the corresponding disulfides to give pyridylsulfur chlorotetrafluorides (SF4 Cl‐pyridines), followed by chloride/fluoride exchange with fluorides. However, the trick in this case is the presence on the pyridine ring of at least one fluorine atom, which is essential for the successful transformation of the disulfides into m ‐and p ‐SF5 ‐pyridines. After enabling the synthesis of an SF5 ‐substituted pyridine, ortho ‐F groups can be efficiently substituted by C, N, S, and O nucleophiles through an SN Ar pathway. This methodology provides access to a variety of previously unavailable SF5 ‐substituted pyridine building blocks. Abstract : It had to be you… A general route for the synthesis of m ‐ and p ‐SF5 ‐substituted pyridines is disclosed. The fundamental synthetic sequence is the same as those reported for ortho ‐SF5 ‐substituted pyridines and SF5 ‐substituted arenes. In this case, however, at least one fluorine atom on the pyridine ring is essential for the success of the transformation. The fluorine substituent can later be substituted by a C, N, O, or S nucleophile (see scheme).